Petrogenesis of Yamato-75032 type diogenites - Yamaguchi, Akira; Barrat, Jean-Alix; Shirai, Naoki (2019)
The Tenth Symposium on Polar Science/Special session: [OA] Antarctic meteorites, Thur. 5 Dec. / 3F Multipurpose conference room, National Institute of Polar Research conference object